Kinetic Study of Mg(II) Adsorption on Activated Coal Bottom Ash - Dwi Putra Wijaya; Chairil Anwar; Rahmat Basuki; Sultan Napoleon; Mayang Fauziah Putri Kuntjahjono (Sorption Studies, 2025)
The research of sadsorption of Mg(II) ions on coal bottom ash as adsorbent has been carried out. The research was conducted by activating the coal bottom ash using concentrated HCl. Characterization of activated coal bottom ash was done by using Fourier Transform Infra-Red (FTIR) spectroscopy and X-Ray Difraction (XRD) analysis. Parameters of metal adsorption examined in this study include the effect of pH, mass of adsorbent, and interaction time. The concentration of each metal ion remaining in the solution after adsorption and desorption was determined using atomic absorption spectrophotometer. The result showed that activated coal bottom ash has been carried out. The optimum conditions for Mg(II) adsorption using 0.3 g coal bottom ash are at pH 5 with 60 minute contact. The Adsorption kinetics follow Ho model pseudo-second order with the rate constant 0.6182 and 0.998 correlation coefficient. These results highlight the potential of activated coal bottom ash as a low-cost, effective adsorbent for water treatment applications.